A virtual engine laboratory for teaching powertrain engineering. Issue 6 (16th June 2017) - Burke, Richard D.; De Jonge, Nicholas; Avola, Calo; Forte, Biagio
Abstract: A virtual engine laboratory application for use in automotive engineering education is proposed to allow the practical teaching of powertrain calibration. The laboratory software is built as a flexible Matlab tool that can easily be transferred for applications in other disciplines and promotes the link between teaching and research.